Hybrid governance in the global south: A case study of collusion within the South African construction industry - Kasipo, Mafaro (Department of Public Law, 2024)
What is the nature of hybrid governance in the Global South? In the African context, a state- centric conceptualisation of governance fails to capture the nuances and realities of governance where non-state actors often fulfil duties that are traditionally the responsibility of the Weberian state. It is against this background that this dissertation seeks to contribute to hybridity literature by exploring the relationships between the state and the construction industry through a case study of collusion in the South African construction industry to build the 2010 FIFA World Cup stadiums. The research goes beyond arguing for a plurality of governance actors and draws on the concept of hybridity to highlight the contestations that characterise the relationship between the different governance actors. The original contribution to hybridity literature made by this research lies in examining how the state and the construction industry enact authority in a setting of hybrid governance. To analyse the process of hybridisation I draw on the concepts of corruption, authority and governmentality as lenses through which to analyse the rationalities, strategies and practices used in the enactment of authority. The research findings reveal that the process of hybridisation as the state and construction industry articulate authority is characterised by contradictions, blurring and boundary-making. The findings suggest that the manifestations of these characteristics during hybridisation is context specific and should be empirically determined